2012
DOI: 10.1186/1476-9255-9-32
|View full text |Cite
|
Sign up to set email alerts
|

The role of protease-activated receptor-2 on pulmonary neutrophils in the innate immune response to cockroach allergen

Abstract: BackgroundSerine proteases in German cockroach (GC) have been shown to mediate allergic airway inflammation through the activation of protease activated receptor (PAR)-2. Neutrophils play an important role in regulating the innate immune response, and are recruited into the airways following GC frass exposure. As such, we investigated the role of PAR-2 in airway neutrophil recruitment, activation and cytokine production following allergen exposure.MethodsWild type and PAR-2-deficient mice were administered a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Corroborating with this evidence, a previous study from our group showed that salivary HBD‐2 levels and PAR 2 expression from gingival crevicular fluid are higher in subjects with chronic periodontitis than in healthy subjects . In addition, PAR 2 activation has also been associated with neutrophil recruitment , another early innate response that plays an important role in periodontal pathogenesis due to the microbicidal machinery of neutrophils. Thus, it can be suggested that PAR 2 downregulation in diabetics with periodontitis might lead to an impaired response against periodontal pathogens and consequently increase the susceptibility and severity of periodontitis.…”
Section: Discussionsupporting
confidence: 66%
“…Corroborating with this evidence, a previous study from our group showed that salivary HBD‐2 levels and PAR 2 expression from gingival crevicular fluid are higher in subjects with chronic periodontitis than in healthy subjects . In addition, PAR 2 activation has also been associated with neutrophil recruitment , another early innate response that plays an important role in periodontal pathogenesis due to the microbicidal machinery of neutrophils. Thus, it can be suggested that PAR 2 downregulation in diabetics with periodontitis might lead to an impaired response against periodontal pathogens and consequently increase the susceptibility and severity of periodontitis.…”
Section: Discussionsupporting
confidence: 66%
“…S. maltophilia induces inflammation and neutrophil recruitment in the murine lung, and activation of both PAR1 and PAR2 has been shown to increase neutrophil recruitment to the lung in vivo, which results in increased tissue damage and impairs the host response (62,63). Our data presented here suggest that StmPr1-induced PAR signaling may contribute to S. maltophilia-mediated inflammation in the lung.…”
Section: Discussionmentioning
confidence: 64%
“…22 TNF-a expression substantially decreased in airway neutrophils from PAR-2-deficient mice, which suggested a role for PAR-2 in neutrophil-derived cytokine production. 23 To further determine the role of PAR-2 in A. fumigatus keratitis, FSLLRY-NH 2 was used to selectively inhibit PAR-2 and then further confirmed the importance of PAR-2 in A. fumigatus keratitis. Results indicated that FSLLRY-NH 2 treatment significantly decreased mRNA levels of IL-1b, TNF-a, IFN-c, and MIP-2 in comparison with infected control corneas.…”
Section: Discussionmentioning
confidence: 99%